LEARNING STRATEGIES OF THE YELLOW BOOK AT SALAF ISLAMIC BOARDING SCHOOLS TO INCREASE ARABIC VOCABULARY - Hidayah, Nurul; Mujiburrohman; Fatimah, Meti (Proceeding of International Conference of Islamic Education, 2023)
This study aims to determine the yellow book learning strategy to increase vocabulary in Arabic. This research method uses a qualitative approach. While the subject of this study was at the Almada-I Darul Fikr Islamic Boarding School in Bandung Beji Andong Boyolali. Collecting data in this study by participant observation, in-depth interviews and documentation. While the data analysis using data reduction, the presentation of the data then draws conclusions. The results of this study indicate that: (1) Learning the yellow book at the Darul Fikr Al-Mada'I Islamic boarding school Bandung Beji Andong Boyolali uses the book of Tafsir and Usul Tafsir, Hadith and Musthalahul Hadith, Aqidah, Fiqh and Ushul Fiqh, Nahwu Shorf, Date, Faroid , Tajwid and Arabic”. (2) The strategy used by ustadz and ustadzah in learning the yellow book is to increase Arabic vocabulary using the sorogan, bandongan, halaqoh methods, discussion, memorization, writing scientific papers, evaluation, classical (3) Supporting and inhibiting factors for learning the yellow book in Islamic boarding schools salaf to increase Arabic vocabulary at the Darul Fikr Al-Mada'I Islamic Boarding School Bandung Beji Andong Boyolali, namely the ability and quality of the ustadz in teaching is also supported by the activeness of the students in learning, the provision of teaching aids/media, the availability of limited learning time and the character diverse students.